Statistical language and speech processing : 4th International Conference, SLSP 2016, Pilsen, Czech Republic, October 11-12, 2016, Proceedings /: 4th International Conference, SLSP 2016, Pilsen, Czech Republic, October 11-12, 2016, Proceedings. (2016) - Unknown
No abstract available